The Efficacy of Topical Combination Amniotic Membrane Stem Cell Metabolite Product (AMSC-MP) and Vitamin E after Microneedling in Photoaging - Agatha Anindhita Ardhaninggar; Dwi Murtiastutik; Sawitri Sawitri; Cita Rosita Sigit Prakoeswa (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Photoaging, also called extrinsic aging, is a premature skin aging mainly resulting from prolonged and extended exposure to ultraviolet (UV) radiation. Amniotic Membrane Stem Cell Metabolite Products (AMSC-MP) are derived from amniotic membranes that contain cytokines and growth factors that have a role in the skin rejuvenation process. Vitamin E is an antioxidant that has a photoprotective effect, so it is expected to reduce the appearance of clinical signs of photoaging. Not only having skin rejuvenation effect, but microneedling is also expected to facilitate the penetration to increase the efficacy of AMSC-MP and vitamin E. This combination is expected to have a better effect on clinical photoaging improvement. Purpose: To evaluate the effect of a topical combination of AMSC-MP and vitamin E after microneedling on the clinical improvement of photoaging compared to previous skin conditions. Methods: Thirty adult women with photoaging topically administered a combination of AMSC-MP and vitamin E after 3 microneedling sessions at 2 weeks intervals. The evaluation of the improvement of the degree of pores, wrinkles, skin tone and dark spots were performed with the Janus-II Facial Skin Scope System. Result: There was a clinical improvement with a statistically significant difference in terms of the degree of pores, wrinkles, polarized black spots, and UV black spots, which were statistically significant differences (p <0.05). Conclusion: The administration of a topical combination of AMSC-MP and vitamin E after microneedling provided clinical improvement in photoaging as supported by the results of Janus analysis of pores, wrinkles, skin tones, polarized black spots, and UV black spots.